Study on Scuffing Test and Data Management of the 18CrNiMo7-6 Gear-4106 Aviation Oil Tribology System - Zhang Hongchun; Zhu Caichao; Wei Peitang; Chen Taimin; Liu Huaiju (Jixie chuandong)
Aiming at the problem that the conventional oil-immersed lubrication condition cannot truly reflect the operating environment of gear oil-injection lubrication, referring to the FZG A/8.3/90 gear scuffing load capacity test method and using oil injection lubrication gear fatigue test bench, the scuffing load capacity test of 18CrNiMo7-6 carburized gears is carried out based on oil injection lubrication condition with 4106 aviation lubricant. Based on the two-parameter Weibull distribution theory, the gear scuffing performance is evaluated under different reliabilities. Furthermore, based on Python language and database SQLite, a gear scuffing test data management system is developed to realize the effective management and efficient utilization of scuffing test data. The results show that under the same working and process condition, the gear scuffing failure FZG load level has 2-3 degree dispersity. Based on GB/Z 6413.1—2003 flash temperature method, it is found that under the condition of 4106 aviation lubricant injection lubrication, for 50%, 90% and 99% reliability, the gear scuffing temperature of shot peening process is 212.55 ℃, 183.22 ℃ and 152.24 ℃ respectively, improving by 1.51%, 7.31%, 14.99% respectively compared with the grinding process state. The developed data management system realizes scuffing test data flow management. Through the fitting function of two-parameter Weibull distribution, the gear scuffing temperature under different reliability can be obtained, which provides an efficient tool for the evaluation of gear scuffing load capacity.